2018
DOI: 10.1186/s40575-018-0064-x
|View full text |Cite
|
Sign up to set email alerts
|

Labrador retrievers under primary veterinary care in the UK: demography, mortality and disorders

Abstract: BackgroundLabrador retrievers are reportedly predisposed to many disorders but accurate prevalence information relating to the general population are lacking. This study aimed to describe demography, mortality and commonly recorded diseases in Labrador retrievers under UK veterinary care.MethodsThe VetCompass™ programme collects electronic patient record data on dogs attending UK primary-care veterinary practices. Demographic analysis covered all33,320 Labrador retrievers in the VetCompass™ database under vete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
40
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 58 publications
12
40
5
Order By: Relevance
“…Male Chihuahuas were significantly more likely to be neutered than female Chihuahuas (31.8% versus 22.0%). This contrasts to the findings of many other breedrelated studies that reported higher proportional neutering in females [13,27,34,35,43,44] although male French Bulldogs were also more likely to be neutered than females [28]. Both Chihuahuas and French Bulldogs are breeds with rapidly rising popularity and consequently youthful populations.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Male Chihuahuas were significantly more likely to be neutered than female Chihuahuas (31.8% versus 22.0%). This contrasts to the findings of many other breedrelated studies that reported higher proportional neutering in females [13,27,34,35,43,44] although male French Bulldogs were also more likely to be neutered than females [28]. Both Chihuahuas and French Bulldogs are breeds with rapidly rising popularity and consequently youthful populations.…”
Section: Discussioncontrasting
confidence: 90%
“…The median age at death of females (10.2 years) was significantly greater than males (6.9 years). A female longevity advantage as a general trend has been reported for dogs previously [26] but this is not universal across all breeds [27,28]. Awareness of a female longevity advantage could assist prospective owners considering acquiring a Chihuahua, especially where the longevity disparity is quite marked.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Forty-seven percent of dogs assessed in the present study were yellow (51/108), 29% black (31/108), and 24% chocolate/liver (26/108). Although chocolate Labrador Retrievers had a significantly shorter lifespan than non-chocolate Labrador Retrievers (McGreevy et al 2018), in the present study, no relationship was observed between the coat colour and obesity (P=0.8949) or genotype (P=0.0682).…”
Section: Resultscontrasting
confidence: 80%
“…Obesity is the second major primary disorder observed in Labrador Retrievers in the United Kingdom (McGreevy et al 2018). As in other countries (Payan-Carreira et al 2015, McGreevy et al 2018, the Labrador Retriever is among the main breeds with the greatest predisposition to obesity in Brazil (Braos et al 2009, Aptekmann et al 2014, Debastiani 2018). In addition, there is no knowledge of studies that have previously evaluated the prevalence of the canine POMC deletion (P187fs) in Brazilian Labrador Retriever.…”
Section: Introductionmentioning
confidence: 97%